The floater's dilemma: use of space by wild solitary Azara's owl monkeys, Aotus azarae, in relation to group ranges. (May 2017) - Huck, Maren; Fernandez-Duque, Eduardo
Abstract : The fate and behaviour of animals that leave their natal group ('floaters') is usually poorly understood, which can limit the understanding of a species' population dynamics. Attempted immigrations can have serious negative effects on residents who therefore may forcibly reject intruders. Consequently, floaters face a dilemma: they need to leave their natal range to find a breeding territory while trying to avoid potentially lethal rejections from established groups. To examine the hypothesis that floating Azara's owl monkeys avoid established groups temporally, we compared time-matched locations of floaters and groups with randomly selected distances. To examine the hypothesis that floaters avoid established groups spatially, we compared the utilization distribution overlap indices (UDOIs) for core areas of floaters and groups with randomly expected UDOIs. Based on average home range sizes and areas of overlap between floaters, we estimated the floater density in the study area to be 0.2–0.5 per group. The temporal avoidance hypothesis was not supported, since time-matched distances were smaller than distances of random locations, and not larger as predicted under this hypothesis. The spatial avoidance hypothesis, in contrast, was supported, with smaller UDOI s for core ranges than predicted. In conclusion, solitary owl monkeys seem to solve the floater's dilemma by trying to stay in relatively close proximity to groups while still avoiding their core ranges. Floaters thus maximize the number of groups with which they have contact, while being able to leave a group's territory quickly if detected by residents. While no marked sex differences in patterns were detected, there was a strong stochastic element to the number of floaters of a particular sex, thus resulting in a locally uneven operational sex ratio. This, in turn, can have important consequences for various aspects of the population dynamics. Highlights: For every 10 breeding pairs, there are two to five floaters that can challenge them. Owl monkey floaters seek proximity to groups. Floaters avoid the core areas of the groups' territories. Male and female floaters have remarkably similar patterns of range use.